Cold sub‐atmospheric and atmospheric pressure plasma for the treatment of Trichophyton rubrum onychomycosis: An in‐vitro study. Issue 6 (19th August 2020) - Shemer, Avner; Daniel, Ralph; Kassem, Riad; Geffen, Yuval; Galili, Eran
Abstract: Previous studies have suggested the applicability of cold atmospheric pressure plasma for the treatment of onychomycosis. Whether delivering cold plasma in sub‐atmospheric pressure would be beneficial for this purpose is yet to be established. The current study aimed to evaluate efficacy of cold sub‐atmospheric and atmospheric pressure plasma in Trichophyton rubrum growth inhibition. Bovine nails infected with T. rubrum were treated by a cold air plasma device, which enables utilizing plasma in sub‐atmospheric pressures (Low = 100 millibar; High = 300 millibar) or atmospheric pressure. The infected foci were exposed to the plasma source directly or indirectly. Treatment with high sub‐atmospheric pressure setting achieved T. rubrum growth reduction of 94.0% and 73.0%, for direct and indirect exposure to the plasma source, respectively ( P < .001). Low sub‐atmospheric pressure setting achieved similar T. rubrum growth reduction of 86.2% for direct exposure to the plasma source ( P < .001), but only marginally significant 58.8% reduction rate for indirect exposure to the plasma source ( P = .056). None statistically significant fungal growth reduction was attained with the use of atmospheric pressure setting. Cold plasma was shown to effectively inhibit T. rubrum nail growth, with sub‐atmospheric pressure setting achieving better outcome than atmospheric pressure.